Professional Socialization in Nursing: An Evolutionary Concept Analysis - MR Din mohammadi; F Rafii; H Peyravi; N Mehrdad (Tehran University of Medical Sciences, 2010)
Background & Objective: Professional socialization is defined as the process of acquiring knowledge and skills and internalizing values, attitudes, and norms to develop professional identity. This process occurs primarily during formal education programs and continues during orientation to hospital settings. The aim of this study was to clarify professional socialization concept and to identify its attributes, antecedents and consequences in nursing context. Methods & Materials: Rodgers;apos evolutionary method of concept analysis was used to facilitate clarification of professional socialization concept in nursing. The search, performed on scientific databases using the keywords: ;apossocialization;apos, ;aposprofessional socialization;apos and ;aposnursing;apos, resulted in findings of a sample of 446 papers covering the period 1995 to 2009 represented the disciplines of nursing and related sciences. After applying inclusion and exclusion criteria, a total of 47 articles and four books were included in the final analysis. The process was audited by two independent experts to ensure neutrality and credibility of the study and to reduce the potentials for bias. Results: The result of the analysis showed that professional socialization is a complex process consisting of four critical attributes: learning, being interactive, developing, and being adaptive. Comprehensive educational programs, competent role models, and provision of adequate field experiences were antecedents for these attributes. The widespread and diverse consequences of professional socialization depend on personal, situational, and organizational factors. Thus, while occurrence of socialization process generates benefits, its nonoccurrence entails severe consequences. Conclusion: Professional socialization process is a complex, diverse, dynamic, ongoing, inevitable, and unpredictable process. This process can have both positive and negative consequences on professional development. However, negative consequences are more prominently documented in the literature. Thus, successful socialization requires establishing facilities in education and practice. The purpose of this revolutionary concept analysis was to focus on significance and how-to-apply ways of the concept in nursing. These findings not only are added to the body of knowledge, but also serve as an important impetus for further theory development and research in nursing.